Why Do Parotid Pleomorphic Adenomas Recur? A Systematic Review of Pathological and Surgical Variables - Dulguerov, Pavel; Todic, Jelena; Pusztaszeri, Marc; Alotaibi, Naif H. (Frontiers in Surgery, 2017)
BACKGROUND The recurrence of pleomorphic adenoma has been extensively debated, mostly in relation to the extent of parotidectomy METHODS A systematic review was undertaken to clarify the surgical and pathological variables related to pleomorphic adenoma recurrence. Inclusion criteria were: English literature, prospective or retrospective studies. Exclusion criteria were: single case reports, reviews and lack of pleomorphic adenoma recurrence data. RESULTS Pathology related variables associated with recurrence include the histological subtype, the thickness and incompleteness of the tumor capsule, pseudopodia, and satellite nodules. Surgery related variables associated with recurrence are the presence of intact margins and tumor puncture or spillage. Other factors are the size of the tumor and the age of patient. Myxoid subtypes of pleomorphic adenoma tend to have incomplete and thinner capsules and to recur more frequently. Surgical variables related to recurrence include positive margins and tumor spillage. CONCLUSIONS Myxoid and/or large pleomorphic adenoma, especially in young patients, should be approached more cautiously to avoid recurrences.